Setting The Parliamentary Threshold (PT) in The Context of Law Number 7 of 2017 Concerning General Elections Based on People's Sovereignty Article 1 Paragraph (2) of The 1945 Constitution of The Republic of Indonesia - Idrus Idrus (Al Ahkam, 2022)
Many policies and regulations (Laws) are made and produced with the aim of realizing democracy. The government's efforts are: First, to amend the 1945 Constitution, namely by adding clear rules. Third, holding general elections as a manifestation of the realization of the revitalization of several political laws with the aim of determining party delegates who will sit in parliamentary seats by taking into account the seat quota, so that the presidential system expected by the 1945 Constitution is realized. Reforms in the field of law that have occurred since 1998 have been institutionalized through the amendments to the 1945 Constitution. The spirit of the amendments to the 1945 Constitution is to encourage the establishment of a more democratic state structure. Amendments to the 1945 Constitution since the reformation were carried out four times; Theoretically, the threshold or also known as the threshold in the electoral system is the minimum support limit that every political party must have in order to get its representative seat in parliament. There are two types of thresholds in elections: the parliamentary threshold and the presidential threshold. The parliamentary threshold is the minimum percentage of the total that must be obtained by every political party that has been legally participating in the election to then be included in the counting of seats in the parliament.Parliamentary Threshold 2009 Election, Article 202 of Law No. 10 of 2008 explains that political parties participating in the election must meet the threshold for obtaining votes of at least 2.5 percent of the number of valid votes nationally to be included in determining the acquisition of seats in the DPR. In the 2014 General Election, the Election Contesting Political Parties must meet the threshold for obtaining votes of at least 3.5% (three point five percent) of the number of valid votes nationally to be included in determining the seat acquisition for members of DPR, Provincial DPRD, and Regency/Municipal DPRD. . Parliamentary Threshold in the 2019 Election, Political Parties Contesting in the Election must meet the threshold for obtaining votes of at least 4% (four percent) of the total number of valid votes nationally to be included in determining the acquisition of seats for members of the DPR". implemented, but how can the democracy materially be implemented based on the philosophy or ideology adopted by a nation or state.Keywords: parliamentary threshold, people's sovereignty, general election